Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.jpcb.8b03870
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Modulations of Electric Fields in Proteins

Abstract: Electrostatic interactions are essential for controlling the protein structure and function. Whereas so far experimental and theoretical efforts focused on the effect of local electrostatics, this work aims at elucidating the long-range modulation of electric fields in proteins upon binding to charged surfaces. The study is based on cytochrome c (Cytc) variants carrying nitrile reporters for the vibrational Stark effect that are incorporated into the protein via genetic engineering and chemical modification. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 71 publications
2
49
0
Order By: Relevance
“…To take into account the effect of an H-bond between OH group and nitrile N atom to the vibrational solvatochromism in an ad hoc manner, Biava et al modified the vibrational Stark effect theory considering two different CN groups, i.e., non-H-bonded and H-bonded nitriles. 336 They are then treated differently so that the net vibrational frequency shift of the CN stretch mode is expressed as a function of the fraction of the H-bonded species, HB The above results and failures in developing a rigorous and systematic theory for vibrational solvatochromism of CN stretching vibration in solutions suggest that the vibrational solvatochromic frequency shifts of the nitrile stretching mode result from various contributions from quadrupole and higher-order multipole terms and non-Coulomb interactions in addition to the dipolar term. By employing the Bio-SolEFP method for the vibrational frequency shift of the IR probe, Błasiak et al demonstrated that the nitrile stretching frequency shift due to Hbonding interaction with surrounding water molecules is determined not only by the contribution of Coulomb interactions but also by the dispersion interactions and the exchangerepulsion contributions.…”
Section: Nitrile Stretchmentioning
confidence: 99%
“…To take into account the effect of an H-bond between OH group and nitrile N atom to the vibrational solvatochromism in an ad hoc manner, Biava et al modified the vibrational Stark effect theory considering two different CN groups, i.e., non-H-bonded and H-bonded nitriles. 336 They are then treated differently so that the net vibrational frequency shift of the CN stretch mode is expressed as a function of the fraction of the H-bonded species, HB The above results and failures in developing a rigorous and systematic theory for vibrational solvatochromism of CN stretching vibration in solutions suggest that the vibrational solvatochromic frequency shifts of the nitrile stretching mode result from various contributions from quadrupole and higher-order multipole terms and non-Coulomb interactions in addition to the dipolar term. By employing the Bio-SolEFP method for the vibrational frequency shift of the IR probe, Błasiak et al demonstrated that the nitrile stretching frequency shift due to Hbonding interaction with surrounding water molecules is determined not only by the contribution of Coulomb interactions but also by the dispersion interactions and the exchangerepulsion contributions.…”
Section: Nitrile Stretchmentioning
confidence: 99%
“…Given a simplified electrostatic description of non-covalent interactions between the vibrational probe and surrounding molecules, the strength of these intermolecular interactions can be assessed by the electric field a target chemical bond feels, as revealed by the VSE [5,13]. The VSE has been extensively applied to study the non-covalent interactions in different types of chemical systems and environments including proteins/enzymes [6][7][8]10,11,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], nucleic acids [34,35], ionic liquids [36,37], biological membranes [38], electrochemical interfaces/surfaces [12,[39][40][41][42][43], and polymers [3,44,45]. Recently, the range of applications has been extended to the investigation of water clusters [46,47] and molecular solids [48].…”
Section: Introductionmentioning
confidence: 99%
“…This new concept of charge reorganization in proteins is consistent with the recent discovery of long range electron conduction in proteins 6 and the finding of long range modulation of electric field in proteins. 7…”
mentioning
confidence: 99%